Simulation of the Heat Current Limitation Algorithm for the Traction Battery Management System - Filatov, V. V.; Klimov, A. V.; Ukhov, I.V.; Podgornyy, A. V. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
The most relevant issue in the field of research of battery vehicles with traction electric drive is the question of the operation of the traction battery (TB). The article discusses the characteristic features of the operation of lithium-ion batteries. The influence of changes in the operating parameters of the TB on the battery calendar life and the occurrence of negative effects is estimated. The algorithm of current limitation in the battery control system is considered. The article describes the principle of operation of the heat current limitation algorithm on the example of a mathematical model.